-51-9x=-2x+95

Simple and best practice solution for -51-9x=-2x+95 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -51-9x=-2x+95 equation:


Simplifying
-51 + -9x = -2x + 95

Reorder the terms:
-51 + -9x = 95 + -2x

Solving
-51 + -9x = 95 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-51 + -9x + 2x = 95 + -2x + 2x

Combine like terms: -9x + 2x = -7x
-51 + -7x = 95 + -2x + 2x

Combine like terms: -2x + 2x = 0
-51 + -7x = 95 + 0
-51 + -7x = 95

Add '51' to each side of the equation.
-51 + 51 + -7x = 95 + 51

Combine like terms: -51 + 51 = 0
0 + -7x = 95 + 51
-7x = 95 + 51

Combine like terms: 95 + 51 = 146
-7x = 146

Divide each side by '-7'.
x = -20.85714286

Simplifying
x = -20.85714286

See similar equations:

| x+7=2(x) | | y-3=4(x+5) | | 3x+11+5x-9=360 | | 2-18/x^2 | | 80+11x-10=360 | | 2x+(-5)=3x+(-1) | | y-7=-5(x+8) | | secx-tanx=cscx-1/cotx | | 2m-0.5=1.7 | | 12y-30=18 | | -4(w+7)=24 | | 8=2x/0.200-x | | y+6=-7(x+5) | | (18-8x)/4x | | -11=x-5-1 | | 2y+4x-3w=19 | | -4x+68=0 | | 15-1(5m-4)=34 | | (x+3)(x+4)(2)=0 | | 3/4×2×12=j | | -38-12x=-8x+18 | | 5x^2-18x+8=0 | | .25=s-5 | | 5x^2-18x+9x=0 | | -7/5b=21 | | 7-7/5b=21 | | 7+x+1=360 | | X+x+1.25=4.75 | | 9/x-2/3=0 | | k+6+2=6 | | =32x+15000 | | h=-16t^2-24+100 |

Equations solver categories